The luminescent quantum efficiency of Cr3+ ions in Cs2NaAlF6 single crystals - Torchia, Gustavo Adrian (2002)
The luminescent quantum efficiency of Cr3+ ions in single fluoride crystal Cs2NaAlF6 was determined by using the simultaneous multiple-wavelength photoacoustic and luminescent experiments method, based on the generation of photoacoustic and luminescence signals after pulsed laser excitation. The luminescent quantum yield for the most important transition between the 4T2→4A2 vibronic levels was found to be 68 ± 3%. This value agrees with that obtained from the ratio of the lifetimes of the corresponding transition at different temperatures.